Relationship Between Intubation and Mortality in COVID-19 Patients with Moderate ARDS, Secondary Bacterial Infection Status - Derya Tatlısuluoğlu (Galenos Yayinevi, 2022)
Objective: In many studies on patients with acute respiratory distress syndrome (ARDS) caused by severe acute respiratory syndrome coronavirus-2, the mortality rate was found to be high in intubated patients. The aim of this study was to try to understand how intubation affects mortality in patients with coronavirus disease (COVID) polymerase chain reaction-positive ARDS and to understand the relationship between intubation and mortality in the patient group whose PaO2/FiO2 is 100-150 mmHg (moderate) and who have difficulty in intubation decision. Materials and Methods: Patient information was obtained by retrospectively examining the hospital computer database and patient files. Three hundred thirteen patients were included in the study. The patients were divided into two groups as intubated and non-intubated according to their intubation status after the first 24 h of their admission to the intensive care unit (ICU) and their intubation status when PaO2/FiO2 was 100-150 mmHg (moderate ARDS). Results: In the group of patients who were intubated after the first 24 h, the number of mechanical ventilator days was 9.15±8.58 (p<0.001), the length of stay (LOS) in the ICU was 14.15±10.33 (p<0.001), and the length of hospital stay was 18.33±12.13 (p<0.05), it was longer and statistically significant compared to the non-intubated group. Additionally, 140 (80.92%) of these patients died (p<0.001). The number of mechanical ventilator days was 8.87±8.51 and the LOS days were 13.53±9.6 in the intubated group with moderate ARDS, which was longer and statistically significant than the non-intubated group (p<0.001). Moreover, in 80 (68.4%) of all intubated patients, 60 (37.5%) of the intubated patients with moderate ARDS had secondary bacterial infection (p<0.001) and mortality rates were higher (p<0.001). Conclusion: All intubated patients with coronavirus disease-2019, including those with moderate ARDS, had a higher rate of secondary bacterial infection, as well as a higher mortality rate.